Poly(ethylene glycol)-b-poly(epsilon-caprolactone) and PEG-phospholipid form stable mixed micelles in aqueous media - Vakil, Ronak (Langmuir : the ACS journal of surfaces and colloids, 2006)
Novel mixed polymeric micelles formed from biocompatible polymers, poly(ethylene glycol)-b-poly(epsilon-caprolactone) (PEG(5000)-b-PCL(x)) and 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-methoxy poly(ethylene glycol) (PEG-DSPE), possess small size and high thermodynamic stability, raising their potential as long circulating carriers in the context of delivery of antineoplastic and antibiotic drugs. Formation of mixed polymeric micelles was confirmed using size exclusion chromatography and 1H NMR NOESY. Steady-state fluorescence measurements revealed depressed critical micellar concentrations indicative of a cooperative interaction between component hydrophobic blocks, which was quantified using the pseudophase model for micellization. Steady-state fluorescence measurements indicated that the mixed polymeric micelle cores possess intermediate micropolarity and high microviscosity. Pulsed field gradient spin-echo measurements were used to characterize micellar diffusion coefficients, which agree well with those obtained using dynamic light scattering. NOE spectra suggested that the hydrophobic polymer segments from individual components are in close proximity, giving evidence for the formation of a relatively homogeneous core. Contrary to one-component PEG(5000)-b-PCL(x) micelles, the mixed polymeric micelles could incorporate clinically relevant levels of the poorly water soluble antibiotic, amphotericin B (AmB). AmB encapsulation and release studies revealed an interesting composition-dependent interaction of the drug with the mixed polymeric micelle core